Clinical characteristics of a large familial cohort with Medullary thyroid cancer and germline Cys618Arg RET mutation in an Israeli multicenter study - Rosenblum, Rachel Chava; Hirsch, Dania; Grozinsky-Glasberg, Simona; Benbassat, Carlos; Yoel, Uri; Ishay, Avraham; Zolotov, Sagit; Bachar, Gideon; Banne, Ehud; Levy, Sigal; Twito, Orit (Frontiers in Endocrinology, 2023)
Objective To determine genealogical, clinical and pathological characteristics of a cohort with Cys618Arg mutation from an Israeli multicenter MTC study.Methods Retrospective database analysis examining RET mutations and comparing Cys618Arg and Cys634Arg/Thr/Tyr subgroups.Genetic testing was performed in 131/275 MTC patients (47.6%). RET mutations were found in 50/131 (38.2%), including Cys618Arg (28/50 cases,56%), and Cys634Arg/Thr/Tyr (15/50,30%). Through genealogical study, 31 MTC patients were found descendants of one family of Jewish Moroccan descent, accounting for 27/28 patients with documented Cys618Arg mutation and 4 patients without available genetic testing. Familial Cys618Arg cases (n=31) and Cys634Arg/Thr/Tyr cases (n=15, from 6 families) were compared. Although surgical age was similar (25.7 vs 31.3 years, p=0.19), the Cys618Arg group had smaller tumors (8.9mm vs 18.5mm, p=0.004) and lower calcitonin levels (33.9 vs 84.5 X/ULN, p=0.03). Youngest ages at MTC diagnosis were 8 and 3 years in Cys618Arg and Cys634Arg/Thr/Tyr cohorts, respectively. Long-term outcome was similar between groups. The Cys618Arg cohort had lower rates of pheochromocytoma (6.5% vs 53.3%, p=0.001) and primary hyperparathyroidism (3.2% vs 33.3%, p=0.01).Conclusions This is the first description of RET mutation distribution in Israel. Of 131 tested MTC patients, Cys618Arg was the predominant mutation. To the best of our knowledge, this is the largest cohort of Cys618Arg mutation described. For Cys618Arg and Cys634Arg/Thr/Tyr cohorts, MTC was diagnosed earlier than expected, likely due to familial genetic screening, and MTC outcomes were similar between groups. International studies are necessary to further characterize the clinical features of Cys618 mutations due to their relative rarity.